Sperm Bundles in the Seminal Vesicle of the Crematogaster victima (Smith) Adult Males (Hymenoptera: Formicidae) - Oliveira, C. M.; Moreira, J. [UNESP]; Gomes, L. F.; Camargo-Mathias, M. I. [UNESP]; Lino-Neto, J. (Entomological Soc Brasil, 2014)
This study establishes the presence of spermatodesm in the seminal vesicles of sexually mature males of Crematogaster victima (Smith). In this species, the spermatozoa are maintained together by an extracellular matrix in which the acrosomal regions are embedded. This characteristic has not yet been observed in any other Aculeata. However, the sperm morphology in this species is similar to that described for other ants. The spermatozoa measure on average 100 mu m in length, and the number of sperm per bundle is up to 256. They are composed of a head formed by the acrosome and nucleus; this is followed by the flagellum, which is formed by the centriolar adjunct, an axoneme with a 9 + 9 + 2 microtubule pattern, two mitochondrial derivatives, and two accessory bodies. The acrosome is formed by the acrosomal vesicle and perforatorium. The nucleus is filled with compact chromatin with many areas of thick and non-compacted filaments. Both mitochondrial derivatives have the same shape and diameters. The presence of sperm bundles in sexually mature males differentiates C. victima from other ants; however, the similarities in the sperm ultrastructure support the monophyly of this insect group.
Keywords: Formicidae; Hymenoptera; spermatodesm; ultrastructure